$\left(p^{\wedge} r\right) \Leftrightarrow\left(p^{\wedge}(\sim q)\right)$ is equivalent to $(\sim p)$ when $r$ is.

  • [JEE MAIN 2022]
  • A

    $p$

  • B

    $\sim\,p$

  • C

    $q$

  • D

    $\sim\,q$

Similar Questions

If statement $(p \rightarrow q) \rightarrow (q \rightarrow r)$ is false, then truth values of statements $p,q,r$ respectively, can be-

Dual of $(x \vee y) \wedge (x \vee 1) = x \vee (x \wedge y) \vee y$ is

$\sim (p \vee q) \vee (\sim p \wedge q)$ is logically equivalent to

The number of ordered triplets of the truth values of $p, q$ and $r$ such that the truth value of the statement $(p \vee q) \wedge(p \vee r) \Rightarrow(q \vee r)$ is True, is equal to

  • [JEE MAIN 2023]

The Boolean expression $\sim\left( {p\; \vee q} \right) \vee \left( {\sim p \wedge q} \right)$ is equivalent ot :

  • [JEE MAIN 2018]